Torted gallbladder causing massive distension and gross necrosis; a rare surgical emergency. (21st August 2013) - Ball, William Robert; Dalmia, Sanjay; Rajamanickam, Shenbaga Kumar; Khan, Mohammed Ayub
Abstract : Gallbladder torsion is rare and is more frequently seen in elderly women. Published case reports comment that diagnosis of this entity can be made preoperatively through imaging with some advocating removal laparoscopically. This case reports an elderly woman who underwent emergency laparotomy for a massively distended gallbladder with suspected cholecystitis. At laparotomy the gallbladder was found to be torted over 360° round its pedicle of the cystic duct and artery. The torsion was so pronounced that the gallbladder was massively distended and grossly necrotic with a high risk of perforation. As the pedicle was long the gallbladder was easily separated form the liver and removed in its entirety. This case presented significant diagnostic and management difficulties. By observing the clinical features in the triad of triads for gallbladder volvulus prompt diagnosis, investigation and treatment can be started for this rare emergency presentation.